From peaceful coexistence to the War of all the People: Cuba and the Cold War in Central America and the Caribbean (1975-1983). - Yordanov, Radoslav (Journal of Iberian & Latin American Studies, 2023)
Building on recent scholarly interest in Latin America's Cold War, this paper breaks new ground in using a broad range of original documents from previously largely overlooked voices – the foreign ministries, parties, and security services agencies of Poland, Hungary, Bulgaria, Germany, the Czech Republic, and Romania – in discussing Cuba's Cold War involvement in Central America and the Caribbean from the First Congress of the Cuban Communist Party until the U.S. Grenada invasion. The candid reports provided by contemporary East European observers help us attain a more nuanced picture of Havana's complex policy dilemmas as it sought to negotiate and navigate between its vast ambitions, limited abilities, Soviet bloc restraint, and the ever-present threat of a U.S. invasion. Finally, further in line with the latest advancements in the globalized Cold War historiography, in hearing the voices of Moscow's junior partners, this article casts the events surrounding the tumultuous period in a broader Transatlantic setting beyond the shadows of the superpowers.